Analisis Dampak Lingkungan dan Penegakan Hukum Pidana: Studi Kasus Kebakaran Pestisida PT Biotek Saranatama di Tangerang Selatan - Rayi Kharisma Rajib; Laily Artia Hanum; Bunga Nirvana3 Nirvana (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The fire at PT Biotek Saranatama's pesticide storage facility in South Tangerang in February 2026 resulted in significant environmental consequences. The fire caused approximately 20 tons of poisoning, with waste carried by the air and polluting rivers. This study aims to examine the environmental consequences and examine the application of relevant criminal sanctions. The approach used is normative juridical, through regulatory review and case investigation. The study results indicate that this incident caused widespread air pollution, the death of airborne biota, and potential public health problems. A legal review indicates that this case is punishable as an environmental crime under Law No. 32 of 2009. This is due to the element of negligence that caused environmental damage due to pollution. Legal enforcement for corporations is necessary to ensure that sanctions are educational and raise awareness of compliance with hazardous materials management standards..